SOSIALISASI PENYAKIT DAN EDUKASI OBAT TERHADAP PELAYANAN PASIEN PENYAKIT HIV PADA PUSKESMAS KEBUN JERUK - Kartika Mariskhana; Arfan Sansprayada (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study was to determine the correlation of Disease and Education Socialization at Kebun Jeruk Health Center. Knowing the correlation relationship of Disease Socialization to Services for HIV Patients. Knowing the correlation of Drug Education on Services for HIV Patients. Then find out the correlation between Disease Socialization and Drug Education on HIV Patient Services. The research method used is the method of observation or survey. The sample was 30 patients randomly selected from all HIV disease patients at Kebun Jeruk Health Center. Data collection was carried out by interview techniques, direct observation, questionnaires, and documentation. Data analysis using simple correlation and multiple correlation methods. The statistical test is used t test and F test, this research is conducted on Monday, March 4 - April 4 2019. The results of the study are as follows; (1) Significant partial influence between Dissemination of Diseases to Ministers HIV Patients at 0.578 or coefficient of determination 57.8% and the remaining 42.2% influenced by HIV Drug Education factors and other factors. (2) Significant partial influence between the Education of Drug for Servants of HIV Patients by 0.369 or determination coefficient 36.9% and the remaining 63.1% is influenced by the factor of Dissemination of Waiter Installation and other factors. (3) Significant simultaneous influence between Disease and Drug Education for Ministers of HIV Patients of 0.879 or 87.9% determination coefficient and the remaining 12.1% is influenced by other factors.